Leukocyte telomere length and mitochondrial DNA copy number associate with endothelial function in aging-related cardiovascular disease - Li, Kangbo; Dai, Mengjun; Sacirovic, Mesud; Zemmrich, Claudia; Pagonas, Nikolaos; Ritter, Oliver; Grisk, Olaf; Lubomirov, Lubomir T.; Lauxmann, Martin A.; Bramlage, Peter; Persson, Anja Bondke; Buschmann, Eva; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background We investigated the association between leukocyte telomere length, mitochondrial DNA copy number, and endothelial function in patients with aging-related cardiovascular disease (CVD). Methods In total 430 patients with CVD and healthy persons were enrolled in the current study. Peripheral blood was drawn by routine venipuncture procedure. Plasma and peripheral blood mononuclear cells (PBMCs) were collected. Cell-free genomic DNA (cfDNA) and leukocytic genomic DNA (leuDNA) were extracted from plasma and PBMCs, respectively. Relative telomere length (TL) and mitochondrial DNA copy number (mtDNA-CN) were analyzed using quantitative polymerase chain reaction. Endothelial function was evaluated by measuring flow-mediated dilation (FMD). The correlation between TL of cfDNA (cf-TL), mtDNA-CN of cfDNA (cf-mtDNA), TL of leuDNA (leu-TL), mtDNA-CN of leuDNA (leu-mtDNA), age, and FMD were analyzed based on Spearman's rank correlation. The association between cf-TL, cf-mtDNA, leu-TL, leu-mtDNA, age, gender, and FMD were explored using multiple linear regression analysis. Results cf-TL positively correlated with cf-mtDNA (r = 0.1834, P = 0.0273), and leu-TL positively correlated with leu-mtDNA (r = 0.1244, P = 0.0109). In addition, both leu-TL (r = 0.1489, P = 0.0022) and leu-mtDNA (r = 0.1929, P < 0.0001) positively correlated with FMD. In a multiple linear regression analysis model, both leu-TL (β = 0.229, P = 0.002) and leu-mtDNA (β = 0.198, P = 0.008) were positively associated with FMD. In contrast, age was inversely associated with FMD (β = −0.426, P < 0.0001). Conclusion TL positively correlates mtDNA-CN in both cfDNA and leuDNA. leu-TL and leu-mtDNA can be regarded as novel biomarkers of endothelial dysfunction.